The evolution of owner-entrepreneurs' taxation: five tax regimes over a 160-year period - Niklas Elert; Dan Johansson; Mikael Stenkula; Niklas Wykman (Örebro University School of Business, 2022)
The institutional literature suggests that long-term tax incentives are crucial for entrepreneurs, but studies on this topic are hampered by theoretical and empirical problems related to how to define and measure entrepreneurial income. We resolve these problems by drawing on a theoretical definition of the entrepreneur as an owner, which enables us to identify entrepreneurship empirically by means of investments made by active owners of closely held firms. Using detailed Swedish tax data, we analyze the tax incentives for such owner-entrepreneur investments from 1862 to 2018, thereby highlighting the evolution of a general institutional phenomenon through a long-run, in-depth, country-specific analysis. We calculate the annual marginal effective tax rate (METR) on capital income for investments, distinguishing between average- and top-income entrepreneurs, and between three sources of finance. We identify five tax regimes that indicate substantial differences in institutional quality over time according to the magnitude of the METR and METR differences between average- and top-income entrepreneurs and across sources of finance. Increased taxation of owner-entrepreneurs helps explain the absence of new large entrepreneurial firms in Sweden after World War II, while improved incentives can be associated with Sweden's recent entrepreneurial renaissance.
Keywords: L25; L26; H21; H31; H32; N44; 330; high-impact entrepreneurship; institutional quality; marginal effective tax rates; tax regimes; tax reforms